Teaching excellence in higher education : challenges, changes and the teaching excellence framework - French, Amanda; O'Leary, Matt (Great Debates in Higher Education, 2017)
The introduction of the Teaching Excellence Framework heralds an era of unprecedented scrutiny and focus on the quality of teaching in universities in England. This book offers inter-disciplinary, evidence-informed discussion around notions of excellence in higher education teaching. It will act as a key stimulus for institutional and sector-wide debates and a reference point for initiatives around the TEF agenda. Drawing on the authentic, grounded experiences of practising HE professionals and complemented by a range of recent case studies, this book offers insight into the pursuit of capturing excellence in the complex and wide-ranging context of HE teaching. It will consider what the repercussions of TEF might mean to those involved in learning and teaching in the sector and how this might impact institutional policy and practice.